2003
DOI: 10.1051/forest:2003071
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the periderm in relation to in situ water absorption rates of oak, beech and spruce fine roots

Abstract: -The water absorption by terminal branch roots of mature oak, beech and spruce trees was measured in situ with miniature sap flow gauges for 11 consecutive days and related to the suberin and lignin content of the fine root periderm. All fine roots contained a well-developed periderm, whereas no primary white roots were present. Mean root water uptake decreased in the sequence beech -spruce -oak. Oak roots contained twice as much suberin and a thicker periderm than beech, and had smaller mean water uptake rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…In this regard, some authors proposed sequestering SOC in subsoils by planting deep rooting plant species that would allocate root-derived SOC to deep soil layers 3 6 . European beech may develop a deep rooting system 20 , and the amount of root biomass and necromass may still be considerably high at soil depths greater than 0.6 m 52 53 . Our results do not confirm these hypotheses, but indicate that the recent tree vegetation influences the SOC mainly in the uppermost subsoil horizons (down to the 35 cm depth).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some authors proposed sequestering SOC in subsoils by planting deep rooting plant species that would allocate root-derived SOC to deep soil layers 3 6 . European beech may develop a deep rooting system 20 , and the amount of root biomass and necromass may still be considerably high at soil depths greater than 0.6 m 52 53 . Our results do not confirm these hypotheses, but indicate that the recent tree vegetation influences the SOC mainly in the uppermost subsoil horizons (down to the 35 cm depth).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the digestion recalcitrance of the insect feeding materials decreases, and moreover, their nutritional richness increases. In oak roots, an amount of up to 128 mg g −1 of dry weight (DM) was found [32].In contrast, the amount of lignin in leaves is only 32 mg g −1 DM [33]. Furthermore, the content of protein and nitrogen in the roots of woody plants such as oak, tends to be lower than that in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that water uptake by the root system of trees is more dependent on the specific uptake rate of the absorbing fine roots (i.e. the driving root‐soil water potential gradient and the radial hydraulic conductivity of the root) than on the total surface area of the root system itself (Leuschner et al , 2003). For example, by comparing dry and moist beech stands, Burk (2006) found that beech had higher surface‐specific water uptake rates in the stand with lower annual precipitation than in the moister stand, despite a lower fine root biomass at the dry site.…”
Section: Discussionmentioning
confidence: 99%